Correlation Between Subcutaneous Fat Thickness And Superficial Surgical Site Infection In Patients Undergoing Open Appendectomy - Mahaseth, Naveen; Shah, Santosh; Sharma, Kritendra Raj (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Surgical site infection (SSI) is a commonly encountered complication in any surgery and is commonly associated with appendicitis. Obesity has been associated with delayed wound healing and risk of infections and this research aims to validate the fact. MATERIAL AND METHODS Prospective observational study was carried out in Universal College of Medical Sciences, Bhairahawa, Nepal, from September 2017 to December 2018 on all cases of appendectomy meeting the inclusion criteria. RESULTS Of total 100 cases of acute Appendicitis, 35% cases developed superficial surgical site infection (SSSI). The development of SSSI in patients with subcutaneous fat thickness (SCFT) of greater that 2.5 cm, between 1.5 cm to 2.5 cm and less than 1.5 cm were 62.5%, 41.9% and 6.1% respectively. Similarly, 40% of patients in grade I obesity group, 63.6% of patients in pre-obese group and 31.1% of patients in normal BMI group developed SSSI. On comparison between SCFT and BMI on a ROC curve, SCFT (0.785) has more AUC than BMI (0.762). CONCLUSION It has been observed that patients with increasing amount of SCFT at incision site had higher chances of developing SSSI. It could also be concluded that though both increased BMI and SCFT had increased frequency of occurrence SSSI, SCFT was more reliable in predicting the chances of SSSI as significant number of cases of SSSI were occurring in normal BMI and pre- obese group.